Rapid learning curve for Solitaire FR stent retriever therapy: evidence from roll-in and randomised patients in the SWIFT trial. (12th February 2015) - Sheth, Sunil A; Jahan, Reza; Levy, Elad I; Jovin, Tudor G; Baxter, Blaise; Nogueira, Raul G; Clark, Wayne; Budzik, Ronald; Zaidat, Osama O; Saver, Jeffrey L
Abstract : Background: In light of recent positive trial data for endovascular therapy in acute ischemic stroke (AIS), stent retriever use by practitioners without prior experience with these devices may become more common. Objective: To assess the safety and efficacy of thrombectomy for AIS using Solitaire for patients treated in the roll-in period of the Solitaire With the Intention For Thrombectomy (SWIFT) trial, which represented the first clinical use of the device for these interventionalists. Methods: Prospectively collected demographic, clinical, and angiographic data on patients treated in the initial roll-in and subsequent randomized phases of the SWIFT study were collected and analyzed. Key statistical analyses were validated by an independent external statistician. Results: Patients in the roll-in period achieved equivalently high rates of reperfusion (55%) compared with those treated with the device in the randomized phase (61%). Rates of adverse events were comparable (13% vs 9%). Rates of good neurological outcome were equivalent between the roll-in and randomized patients treated with Solitaire (63% vs 58%). Including the roll-in patients strengthened the conclusions of the study, that reperfusion rates without symptomatic hemorrhage with Solitaire were greater than with Merci (59% vs 24%, p<0.001). Conclusions: Thrombectomy in AIS using the Solitaire stent retriever device can be performed safely and effectively when used by experienced neurointerventionalists without previous experience with the device. Trial registration number: The SWIFT study is registered with ClinicalTrials.gov, number NCT 01054560.